A Proton-Triggered Cascade Reaction Involving a Heavy p-Block Multiple Bond: Transformation of the Diphosphene C5Me5P=PC5Me5 into the Cationic Cage [C10Me10P2H](+) - Presly, O; Davin, T; Green, M; Kilby, R; Mansell, S; McGrady, J; Russell, C (2008)
Protonation of one of the phosphorus centers of the diphosphene C 5Me5P=PC5Me5 triggers a remarkable cascade reaction leading to the direct formation of a C10P 2 cage. Calculations suggest that the key mechanistic feature is the proximity of a C=C π-system to a developing positive charge on one of the phosphorus centers. © Wiley-VCH Verlag GmbH and Co. KGaA, 2008.